Dampak Penambangan Pasir Terhadap Kualitas Air Sungai Bulango - Hendra Bawu; Sri Maryati; Daud Yusuf (Jurnal Penelitian Pendidikan Geografi, 2023)
Several locations along the Bulango River are utilized by the community for sand mining. The decline in river water quality is one of the impacts of sand mining on the environment. The purpose of this study was to determine the impact of sand mining on the physical quality of water in the Bulango River, North Bulango District, Bone Bolango Regency. Analysis of physical parameters carried out in the field, namely temperature, light intensity, and total suspended solids which was carried out in the laboratory. The results showed that the total suspended solids (TSS) at location II and location III at sunny weather were higher than at location I. Light intensity at location II and location III was lower than at location I. TSS parameters during rainy weather at location I, location II, and location III exceed the quality standards for classes 1 to 4. When the weather is sunny, the TSS values for locations II and location III exceed the quality standards for classes 1 and 2.